2021
DOI: 10.1097/mou.0000000000000957
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 on urology office visits and adoption of telemedicine services

Abstract: Purpose of reviewThe purpose of this review article is to discuss the impact of Coronavirus Disease 2019 (COVID-19) on the evolution of telemedicine use for urology office visits. Recent findingsThe COVID-19 pandemic has caused a dramatic change in the delivery of healthcare. Fraught with numerous barriers previously, the need for healthcare delivery during a time of social distancing and increased healthcare requirements drove the adoption of telemedicine forward. This 'trial period' over the last year has al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 29 publications
(33 reference statements)
0
10
0
Order By: Relevance
“…8 Other studies have found that some patients preferred telemedicine, owing to spending less time waiting to see practitioners, travelling to appointments, and eliminating the need to find transportation to attend appointments. [9][10][11][12] Despite not being face-to-face, the majority of patients voice that they were able to adequately communicate their uncomplicated medical concerns over virtual means and have them understood or addressed by their physicians. 9 Medical practitioners have also reported high satisfaction rates with the adoption of telemedicine.…”
Section: ) What Are the Benefits And Limitations Of Virtual Platforms...mentioning
confidence: 99%
See 4 more Smart Citations
“…8 Other studies have found that some patients preferred telemedicine, owing to spending less time waiting to see practitioners, travelling to appointments, and eliminating the need to find transportation to attend appointments. [9][10][11][12] Despite not being face-to-face, the majority of patients voice that they were able to adequately communicate their uncomplicated medical concerns over virtual means and have them understood or addressed by their physicians. 9 Medical practitioners have also reported high satisfaction rates with the adoption of telemedicine.…”
Section: ) What Are the Benefits And Limitations Of Virtual Platforms...mentioning
confidence: 99%
“…13 Many clinics have also reported a decrease in wait times to see practitioners, likely owing to the increased efficiency of virtual models of care. 10,12 However, there are limitations to virtual medicine in urology that have been identified. Some patients regard face-to-face interactions as an important way to foster a trusting, therapeutic relationship.…”
Section: ) What Are the Benefits And Limitations Of Virtual Platforms...mentioning
confidence: 99%
See 3 more Smart Citations